Vigilancia ambiental de la circulación de poliovirus en tres municipios considerados como punto transitorio de migrantes en Colombia 2017-2019 - María Mercedes González-De Schroeder (Asociación Colombiana de Infectología, 2021)
Objective: To determine the circulation of poliovirus in three municipalities considered as transitory points for migrants in Colombia.Material and Method: Wastewater samples (n = 36) were collected from border municipalities, selected for greater transit of regular and irregular migrants, in the period between 2017-2019. The samples were concentrated and cultured following the World Health Organization (WHO) environmental surveillance algorithm for poliovirus circulation. Molecular identification was performed by polymerase chain reaction using group-specific, serotype and sabin vaccine strain primers.Results: The presence of non-polio Enterovirus (NPV) was detected in the environmental samples obtained and no circulation of poliovirus derived from the vaccine or wild poliovirus was found in the three evaluated municipalities; However, in two previous studies published by Gonzales et al with a similar methodology in 2005 and 2015 evaluating the wastewater of the city of Armenia-Quindío; It was possible to identify the presence of virus derived from vaccine, with negative results for the identification of wild poliovirus.Conclusions: The findings indicate that the wastewater monitoring system in order to determine the presence of viruses is a useful tool to carry out environmental surveillance.